Development of Mathematical Comic to Improve Student Learning Achievement - Amalliyah, Nor; Setiawan, Wahyu; Hidayatullah, Bagus; Malik, Fatus Atho’ul; Nurwahid, Mohammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to develop mathematics comic learning media that is valid, practical, and effective in improving student learning outcomes. The research background is based on problems in mathematics learning, where abstract concepts are often difficult for students to understand. Mathematics comics, as a visual medium that combines narrative and illustration elements, have the potential to present mathematical concepts in a more-interesting and easy to understand manner, thereby increasing student motivation and learning outcomes. This research uses the development research (R&D) method with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The research was carried out at Bustanul Hikmah Islamic Vocational School, involving class XI students as test subjects. Data collection instruments include expert validation questionnaires, student response questionnaires, and learning outcomes tests. The results of expert validation show that the mathematics comic developed meets valid criteria in terms of content, construction and language. The results of the practicality trial show that the mathematics comic is easy to use, the material is presented clearly, and attracts students' interest. Analysis of learning outcome data shows a significant improvement after using mathematics comics. Thus, it can be concluded that the mathematics comics developed are valid, practical and effective for improving student learning outcomes. This mathematics comic can be an innovative and interesting alternative learning media to improve the quality of mathematics learning.